Educação de jovens e adultos: uma escuta dos desafios docente na prática da inclusão no ensino fundamental nas disciplinas de Língua Portuguesa e Matemática em Bragança-PA - VILA NOVA, Jennifer Damiane Baia (2021)
The study presented here aimed to investigate how the educational practices of inclusion for students of EJA in a Elementary School in the disciplines of Portuguese Language and Mathematics, since the literature has raised discussions about the great pedagogical difficulty of the teacher to develop in the student disabled learning for their social ability. The study was conducted in a class of 3rd Stage of Elementary School with two teachers of specific subjects (Portuguese and Mathematics) and the teacher of AEE. Observations were made in the classroom, as well as narrative interviews with these professionals, their narratives are anchoring the texture developed in the study. The methodological outlines are anchored in qualitative research in the conceptions of BOGDAN AND BINKLEN (1994), CASTRO (2017) and LUKDE and ANDRÉ (2015). The results show the great difficulty of teachers in developing strategies to address the teaching of students with educational needs in the form of EJA, since these teachers do not find support in their work partners and have no training focused on inclusive education.